Strategi Pemasaran Pada Usaha Jasa Wedding Ren Organizer - Ihwan Fadilah; Dian Marlina Verawati; Ivo Novitaningtyas (Jurnal Bisnis dan Kewirausahaan, 2024)
This research aims to identify the current business conditions of REN Organizer using the Business Model Canvas (BMC) approach and then develop a new business model using SWOT analysis. SWOT analysis is used to determine internal conditions based on the service marketing mix and external conditions with economic, political, social, technological, environmental, and legal factors. The analysis results obtained in the form of REN Organizer's business conditions show that the business has strengths and several opportunities that have not been maximized. Therefore, the strategy formulation obtained includes increasing promotions through social media, improving products by increasing vendor collaboration according to client needs and adding other sources of capital to improve product quality and resources. This strategy aims to develop a new business model for REN Organizer to become a more developed Wedding Organizer.